Prosthetic rehabilitation of large mid-facial defect with magnet-retained silicone prosthesis - Kirti Jajoo Shrivastava; Saurabh Shrivastava; Surendra Agarwal; Anjali Bhoyar (Wolters Kluwer Medknow Publications, 2015)
Rehabilitation of maxillofacial defect patients is a challenging task. The most common prosthetic treatment problem with such patients is, getting adequate retention, stability, and support. In cases of large maxillofacial defect, movement of the prosthesis is inevitable. The primary objectives in rehabilitating the maxillofacial defect patients are to restore the function of mastication, deglutition, speech, and to achieve normal orofacial appearance. This clinical report describes maxillofacial prosthetic rehabilitation of large midfacial defect including orbit along with its contents, zygoma and soft tissues including half of the nose, cheeks, upper lip of left side, accompanying postsurgical microstomia and orofacial communication, which resulted from severe fungal infection mucormycosis. The defect in this case was restored with magnet retained two piece maxillofacial prosthesis having hollow acrylic resin framework and an overlying silicone facial prosthesis. The retention of prosthesis was further enhanced with the use of spectacles. This type of combination prosthesis enhanced the cosmesis and functional acceptability of prosthesis.